Anxiolytic and anti-inflammatory role of thymoquinone in arsenic-induced hippocampal toxicity in Wistar rats. Issue 6 (June 2018) - Firdaus, Fakiha; Zafeer, Mohd Faraz; Ahmad, Masood; Afzal, Mohammad
Abstract: Arsenic (As) is a widely existing metalloid in the biosphere. Drinking water contamination by arsenic is a major route of human exposure, either by natural means or through industrial pollution. Numerous evidence form earlier reports suggest that arsenic exposure causes cerebral neurodegeneration which initiates behavioral disturbances concomitant to psychiatric disorders. Also, mood disorders in humans as well as in animals correlate with arsenic exposure; the present study is carried out to implore the neuroprotective potential of thymoquinone (TQ) in arsenic-stressed rats. TQ is an active component of Nigella sativa (Kalonji) seed oil. Arsenic exposure in the form of sodium arsenate (10 mg/kg/day; p.o) caused neurobehavioral deficits as evidenced by changes in locomotion and exploratory behavior in open-field and elevated plus maze tasks. Alongside this, arsenate also elevated hippocampal oxidative stress parameters like lipid peroxidation (TBARS) and protein carbonyl formation with a decrease in superoxide dismutase (SOD) and reduced glutathione (GSH) content. Genotoxicity assessment by Comet assay also showed prominent levels of DNA damage. Furthermore, arsenic also elevated hippocampal cytokine levels, TNF-α and INF-γ. However, TQ supplementation (2.5 and 5 mg/kg/day, p.o) preceded three days before arsenic administration, significantly attenuated arsenic-associated anxiogenic changes which majorly attributed to its antioxidant and anxiolytic potential. Also, TQ pre-treated rats expressed positive shifts in the hippocampal oxidative stress and cytokine levels with decreased DNA fragmentation. Thus, this study concludes that TQ might serve as a strong therapeutic agent for management of anxiety and depressive outcomes of arsenic intoxication.